Handbook of ecological restoration (Cambridge University Press, 2002)
Restoration Practice details state-of-the-art restoration practices in a range of biomes within terrestrial and aquatic (marine, coastal, and freshwater) ecosystems. Policy and legislative issues on all continents are outlined and discussed. The Handbook of Ecological Restoration is an invaluable resource to everyone concerned with the restoration, rehabilitation, enhancement or creation of habitats in aquatic or terrestrial systems throughout the world